Electronic characterisation of atomistic modelling based electrically doped nano bio p‐i‐n FET. Issue 5 (1st September 2016) - Dey, Debarati; Roy, Pradipta; De, Debashis
Abstract : In this study, electrically doped bio‐molecular p‐i‐n field‐effect transistor (FET) is designed and its electronic properties are investigated. Density functional theory along with non‐equilibrium Green's function based first principle approach is used to design the bio‐molecular FET at sub‐atomic region. Three Adenine and two Thymine molecules are attached together to form 6.24 nm long and 1.40 nm wide bio p‐i‐n FET. This device is attached with two platinum electrodes and wrapped with a metallic cylindrical gate at high vacuum. Intrinsic n and p regions can be made possible within a bio‐molecular device at room temperature by electrical doping without explicit dopants, which leads to conduct current by the device both in forward and reverse bias. The various quantum mechanical properties have been calculated using Poisson's equations and self‐consistent function for the bio‐molecular FET. Among these various quantum mechanical properties, the authors obtain high quantum transmission along with satisfactory current for the proposed device during the room temperature operation. The goal of this study is to highlight the design of a bio‐molecular p‐i‐n FET with satisfactory large current using ultra low power dissipation.